Respuesta :
Answer:
The correct answer is,
3x² - 30 x + 63 = 3(x - 3)(x - 7)
Step-by-step explanation:
The given polynomial is 3x² - 30 x + 63
Factorization of 3x² - 30 x + 63
Splitting method
3x² - 30 x + 63 = 3(x² - 10 x + 21) (taking 3 as common)
= 3(x² - 3 x - 7x + 21) (middle term splitting)
= 3[x (x - 3) -7(x - 3)] (taking x and -7 as common)
= 3[(x - 3)(x - 7)]
Therefore 3x² - 30 x + 63 = 3(x - 3)(x - 7)
The correct answer is 3(x - 3)(x - 7)
Answer:
3(x-3)(x-7)
Step-by-step explanation:
We have given a expression.
3x²-30x+63
We have to calculate the factor of given expression.
taking 3 common from given expression, we have
3(x²-10x+21)
Splitting the middle term of given expression, we have
3(x²-3x-7x+21)
Making groups , we have
3(x(x-3)-7(x-3))
Taking (x-3) as common, we have
3(x-3)(x-7) which is the answer.